Map of Slave River : Ft. Smith to Resolution, Northwest Territories - Canada. Office of the Surveyor General (Cartographer, Compiler) (Department of the Interior, Topographical Survey of Canada, 1928)
This is a topographic map of Slave River, NT area in 1928 showing gravel bars, routes, settlements, police stations, trading posts, hospitals, missions, and more. It includes notes on relief, vegetation and soil. "Sheet No. 6" Scale 1:253,440, or 4 miles to 1 inch. Relief shown by hachures and notes. Depth shown by soundings. Shows gravel bars, routes, settlements, Indian villages, police stations, trading posts, hospitals and missions. Includes notes on relief, vegetation and soil, as well as distance table and table on rapids. Insets: Ft. Smith -- Fitzgerald. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .